Impact of Social Fund on the Welfare of Rural Households : Evidence from the Nepal Poverty Alleviation Fund - Parajuli, Dilip; Acharya, Gayatri; Chaudhury, Nazmul; Thapa, Bishnu Bahadur (World Bank, Washington, DC, 2012)
The Nepal Poverty Alleviation Fund is a World Bank supported community-driven development program. Its objective is to improve rural welfare, particularly for groups that have traditionally been excluded for reasons of gender, ethnicity, caste, and location. Since its launch in 2004, the Fund has covered the 40 poorest districts of the country, supported some 15,000 community organizations, and benefited more than 2.5 million people. This paper attempts to estimate the impact of this large-scale program using a randomized phase-in approach, in which certain localities are randomly selected for earlier intervention than others. Using two rounds of survey data and a difference-in-difference combined with instrumental variable estimation method, it finds statistically significant causal impact of the program on key welfare outcomes. The treatment-on-the-treated estimate on real per capita consumption is 19 percent growth. Other impacts include a 19 percentage points decline on incidence of food insecurity (defined as food sufficiency for six months or less) and a 15 percentage points increase in the school enrollment rate among 6-15 year-olds. Impacts (positive or negative) are yet to be detected on indicators associated with child malnutrition, social capital, and empowerment. The policy implications of these results should be of interest to the government and to development partners in determining what may be effective instruments to deliver services to marginalized communities in what remains a fragile and difficult political environment.